PENDIDIKAN KEAGAMAAN UNTUK MEMBENTUK KERUKUNAN ANTAR UMAT BERAGAMA DI MEDOWO KANDANGAN KEDIRI - Ali Mustofa (Nazhruna: Jurnal Pendidikan Islam, 2020)
Religious education is education that gived knowledge and forms attitude, personality and in practicing religious teaching conducted in their ife. Theta three religious adhered by Mendowo people , they are Islam, Hindu, and christian. The eople conducted their religious activities in harmony though they adhere different religion. The research result shows that such religious education in Mendowo village as routinely reitation in mosque, dzikir, weekely reitation door to door, giving place for learning alqu'an in each village. It is for Islam. For Hindu, there are legenan, pasraman, and pacalang. Cristian has sunday school in church, door to door worship done in Thrusday which is called spiritial worshipers. The harmony between the ummah can proved by together in worship on the village celebration, helping each other in the moment of holiday each religion, and community self-help on the house building, street, grave, and village.